Spis lenników księstwa żagańskiego z 1719 roku = The vassal census of 1719 in the Duchy of Sagan - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Conducting vassal censuses in feudal duchies was connected with bestowing the continuing vassal rights on lords of the lands. After 1629, in Silesia's feudal duchies the censuses were conducted during or shortly after a vassal diet convened to pay homage to the duke. Since 1646 the Duke of Sagan came from the house of Lobkowitz. After the thirty-year war, the land censuses were part of the Habsburg court's centralist policy of under which coherent administration structures were built in the provinces of th Czech Kingdom and the very Roman Empire of the German Nation.
Keywords: Księstwo Żagańskie - historia - 12-18 w.; spis lenników